INVENTARISASI HAMA DAN PENYAKIT YANG BERASOSIASI PADA TALAS BENENG (Xanthosoma undipes K. Koch) DI KAWASAN GUNUNG KARANG KABUPATEN PANDEGLANG PROVINSI BANTEN - Tubagus Bahtiar Rusbana; Andree Saylendra; Rafael Djumantara (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2016)
The objective of the research was to inventarize pests and diseases that associate with Xanthosoma undipes K. Koch at Mount Karang, Pandeglang, Banten Province. The research was conducted at field of Xanthosoma undipes K. Koch at Mount Karang and Biotechnology Laboratory of Untirta in Serang from May until July 2015. Samples of the Xanthosoma undipes K. Koch were choosen by purposive sampling methods from several points around Mount Karang. Several types of pests, predators, and diseases were found in the cultivation field of Xanthosoma undipes K. Koch. The pests were mantises, grasshoppers, snout beetles, long-horned grasshopper, big eyes dragonfly, ants, cockroaches, spiders, and butterflies. The predators including parasites were ants, flies, stone flies, and crickets. Two diseases were found i.e. leaf blight caused by Phytophtora colocasiae and sooty mold disease caused by Capnodium sp. The study also revealed that pests and diseases were also found in the storage process (post-harvest). Some warehouse pests such as pillbugs, ants and mites were found. The disease found were stem rot disease caused by Sclerotium rolfsii and soft rot caused by Lasiodiplodia theobromae.Keywords: Xanthosoma undipes K. Koch, Pest and diseases